Effects of simulated acid rain on rhizosphere microorganisms of invasive Alternanthera philoxeroides and native Alternanthera sessilis - He, Mengying; Hua, Zexun; Chen, Hanying; Liu, Yao; Li, Yue; Zhang, Zhen (Frontiers in Microbiology, 2022)
Acid rain not only has serious harm to the environment, but also has the same threat to plants, but the invasive plant Alternanthera philoxeroides still grows well compared to the native plant A. sessilis under acid rain stress. However, the underlying mechanism of resistance to the acid rain environment in invasive A. philoxeroides remains unclear. In the current study, we comparatively analyzed the plant physiological characteristics, soil physicochemical properties, and rhizosphere microbial communities of invasive A. philoxeroides and native A. sessilis under different pH condition. The simulated acid rain had a significant inhibitory effect on the morphological and physiological traits of A. philoxeroides and A. sessilis and reduced the soil nutrient content. However, A. philoxeroides was more tolerant of acid rain. Compared with CK, simulated acid rain treatment at pH 2.5 significantly increased the Chao1, ACE, and Shannon indexes of A. philoxeroides microorganisms. Under simulated acid rain treatment at pH 2.5, the fungal flora Chao1, ACE and Shannon index were significantly higher than those of CK by 14.5, 12.4, and 30.4%, respectively. The dominant bacterial phyla of soil bacteria were Proteobacteria, Actinobacteria, Bacteroidota, Actinobacteria, Firmicutes, Myxococcota, Chloroflexi, Patescibacteria, Gemmatimonadota, Verrucomicrobiota, and Armatimonadota. The dominant fungi were Ascomycota, Basidiomycota, Rozellomycota, and Olpidiomycota. The bacterial and fungal diversity and structure of A. philoxeroides and A. sessilis showed the greatest difference between the pH 2.5 treatment and CK. Redundancy analysis showed that electrical conductivity (EC) and total phosphorus (TP) were the main factors changing the bacterial communities, and available phosphorus (AP), organic matter (OM), EC, and pH were the main factors changing the fungal communities. This study contributes to the microbial community structure of the invasive plant A. philoxeroides and provides a theoretical basis for studying the invasion mechanism of invasive plants under acid rain.